Fuel retention and carbon deposition on beryllium marker tiles from JET tokamak main chamber limiters investigated by ion beam analysis. (1st December 2022) - Tsavalas, P.; Lagoyannis, A.; Mergia, K.; Axiotis, M.; Harissopulos, S.; Provatas, G.; Fazinić, S.; Tadić, T.; Widdowson, A.; Rubel, M.; Contributors, JET
Abstract: The JET tokamak with the ITER-like wall is operated with arrays of castellated beryllium (Be) limiters in the main chamber. In several locations Be marker tiles were installed for erosion-deposition studies. The castellation sides and the plasma-facing surfaces (PFSs) of Be marker tiles from three different locations of the JET main chamber, from the experimental campaigns 2011–12 (ILW-1) and 2013–14 (ILW-2), were analysed, employing 2 H and 3 He micro-beams in order to determine carbon (C) impurity deposition and deuterium (D) retention. The deposited C and D amounts on the castellation sides (up to 1.5 mm deep into the groove) were assessed with respect to the ion/electron drift direction. Both the C and D amounts on the investigated castellation sides either stay constant or reduce with depth from the edge of the PFS. No systematic difference is observed in the C deposition or D retention on the different castellation sides of each sample with respect to the ion/electron drift direction. C and D content is found to be lower on the PFS than on surfaces in the gaps of castellation for the majority of the samples. The C amount is, in general, higher than the D one. No systematic correlation between the C and the D amounts has been observed.